The Effect of Variation of Corn Comb Fiber Composition on The Physical Properties of Biofoam with The Addition of Aerogel Silica - Tiara Widiastuti; Roniyus Marjunus; Agus Riyanto; Dwi Asmi (Journal of Energy, Material, and Instrumentation Technology, 2023)
Styrofoam has many negative impacts because it harms health, pollutes the environment, and cannot decompose in nature. Efforts have been made to develop biofoam derived from natural kinds of stuff to reduce the harmful effects of styrofoam. So that they are safer and do not pollute the environment. Biofoam in this study was made from tapioca starch, corncob fiber, a binding polymer in the form of Polyvinyl Alcohol (PVA), and a superhydrophobic agent in the form of silica aerogel. This research was conducted to determine the effect of variations in the composition of corncob fiber on the physical properties of biofoam with the addition of silica aerogel. The production of corncob fiber was carried out in two stages, namely using 10% NaOH to remove lignin and bleaching using 10% H2O2 to bleach the fibers, which were then combined into the biofoam mixture. The production of biofoam used the thermopressing method with a temperature of 150° and pressed for 4 minutes with fiber variations of 13.75g, 16.25g, 18.75g, and 21.25g. Add conclusion of the research is 18.75 g of fiber with a water absorption value of (1.2 ± 0.2)%, a density of (0.5 ± 0.1)g/cm3, and a compressive strength of 3.60 MPa.